Influencia de um programa de esporte educacional com base no atletismo sobre o desenvolvimento motor e social de crianças de 8 a 11 anos de idade - Ferreira, Amanda Cristina de Moura (2014)
The aim of this study was to investigate experimentally the influence of a motor intervention program within the sport education based on athletics on motor and social development of children. The study included 48 subjects of both sexes, aged from 8 to 11. As measuring instruments Testing of Gross Motor Development 2 (TGMD-2) and (SSRS-BR) Rating System Social Skills were used. Two groups were delineated for the program: experimental group, in which 25 children participated in athletics lessons for 15 weeks with two sessions per week lasting two hours each, and the control group, with 23 children who did not participate in the program. Data collection occurred before and after the development of the lessons. For data analysis we used descriptive statistics to Kolgomorov-Smirnov test to verify the normality, the Mann Whitney U test for comparison between groups and the Wilcoxon test for comparison of two moments. We adopted a significance of P ? 0.05. The results of TGMD-2 after the program indicated that 28% of children in the experimental group (EG) were rated above average, 64% average and 8% were considered below the average of the standardized test. In the control group (GC) 1.4% of children were rated above average, 65.2% average and 1.4% below the average. In both groups no child reached motor development ranked higher, much higher, very poor or poor. There has been significant gains in some skills when comparing pre and post-test. The EG showed significant improvement in skills gallop (p = 0.008) and fold (p = 0.01). The CG showed progress in the ability to run (p = 0.003), jump on one leg (p = 0.039) and kick (p = 0.008). At post-test there was a significant difference in the abilities of receiving (p = 0.0046) and roll (p = 0.046). In these two skills the children of GE were higher when compared with the CG. In comparing the two periods SSRS-BR, EG showed a significant difference in global score of social skills (p = 0.0014) and the empathy factor / affectivity (p = 0.016). These two categories of GE children were better at posttest compared with the pretest. The CG presented differences in global score of social skills (p = 0.000) and in other skills empathy / affection (p = 0.001) liability (0,002) self (0.001) and assertiveness (0.005). In all categories the CG children were higher at posttest compared with the pretest. In summary, considering that after 15 weeks it was possible to show some improvement in motor performance of children, we can bilieve that participation in similar medium and long term programs may confirm significant improvements in motor development and social skills of children.